Constitutional origins, structure, and change in federal countries - Kincaid, John, 1946-; Tarr, G. Alan (George Alan); Forum of Federations; International Association of Centers for Federal Studies (Montreal [Que.] : Published for Forum of Federations and International Association of Centers for Federal Studies by McGill-Queen's University Press, 2005)
Annotation Providing examples of diverse forms of federalism, including new and mature, developed and developing, parliamentary and presidential, and common-law and civil law, the comparative studies in this volume analyse government in Australia, Belgium, Brazil, Canada, Germany, India, Mexico, Nigeria, Russia, South Africa, Switzerland, and the United States. Each chapter describes the provisions of a constitution, explains the political, social, and historical factors that influenced its creation, and explores its practical application, how it has changed, and future challenges, offering valuable ideas and lessons for federal constitution-making and reform.
A global dialogue on federalism, conceptual framework / Raoul Blindenbacher and Cheryl Saunders -- Constitutional origins, structure and change / G. Alan Tarr -- Commonwealth of Australia / Cheryl Saunders -- Kingdom of Belgium / Kris Deschouwer -- Federal Republic of Brazil / Celina Souza -- Canada / Rainer Knopff and Anthony Sayers -- Federal Republic of Germany / Jutta Kramer -- Republic of India / Akhtar Majeed -- United Mexican States / Juan Marcos Gutiérrez González -- Federal Republic of Nigeria / Ignatius Akaayar Auya and Dakas C.J. Dakas -- Russian Federation / Marat Salikov -- Republic of South Africa / Nico Steytler -- Swiss Confederation / Nicolas Schmitt -- United States of America / G. Alan Tarr -- Comparative observations / John Kincaid.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Federal government; Constitutional history; Comparative government; Fédéralisme.; Histoire constitutionnelle; Institutions politiques comparées.; federations; comparative politics; POLITICAL SCIENCE -- Government -- State & Provincial; POLITICAL SCIENCE -- Constitutions; Comparative government; Constitutional history; Federal government; Föderalismus